A bond energy theory to analysis the melting temperature and Debye temperature of nanoscale solids - Singh, Madan; Ramoeta, Paul (International Journal of Engineering and Technology, 2026)
Based on bond theory model and surface effects, a size dependent theory is discussed to study the melting temperature and Debye temperature of nanoscale materials. The number of atoms on the surface to the total number of atoms in nanosolid is analysed in terms of size and shape factor of nanomaterials. The variation of melting temperature and Debye temperature is reported for spherical, tetrahedral, hexahedral and octahedral shapes nanomaterials. It is found that the melting point and Debye temperature decrease as the particle size is reduced. The results studied are compared with the available experimental and simulation data. A good agreement between the present calculated results and the results reported by earlier scholars confirm the strength of the theory.